Preparedness for Interprofessional Learning: An Exploratory Study Among Health, Social Care, and Teacher Education Programs - Almendingen, Kari; Molin, Marianne; Šaltytė Benth, Jūratė (Journal of Research in Interprofessional Practice and Education)

(untitled) (Canadian Institute for Studies in Publishing Press (Simon Fraser University at Harbour Centre), 2021)
Background: Interprofessional learning (IPL) research is mainly restricted to health students. The purpose of this study was to assess the IPL preparedness of students from health, social care, and teacher education programs.Methods and findings: This project comprised an exploratory cross-sectionalstudy and online questionnaire. Of the 221 students included, the majority hadlearned about their own future role. In contrast, less than 20 percent had learnedabout other roles.Conclusions: This study suggests that teacher education and health and social carestudents were not equally prepared for IPL. Future research should explore howeducators may balance an unequal understanding of roles among students.